A retextualização como instrumento de manipulação no discurso jurídico penal - Agueda Bueno Nascimento Ashikawa (2007)
This work shows an analysis of a transformation phenomenon of a text into another (re-textualization) from the Textual Linguistics perspective. It focuses on the transformations occurred during the "Testimony genderbuilding testified by various suspects/defendants to Police Officers/Judges, both in Police Stations and Tribunals. The re-textualization activities analyzed are the ones that occur during official audiences, where a dialogical oral text - built by the law professional and the person by him interrogated, is converted into an oral monological text,produced exclusively by the law professional, who dictates it online to the notary who, in turn, consigns it, without interferences, in the "Testimony" (written statement that will instruct the courts Inquiry/Process records). The linguistic phenomena analyzed in this study, which emerged during the transformation of speech into writing, make it clear that the Police/Judicial Inquiry constitutes a kind of "asymmetric interaction", inwhich the law professional directs, commands the other's speech. Thus, this work aims at demonstrating that the criminal judicial speech, built by the transformation phenomenon of an oral into a written text during asuspect/defendant's "Oral Testimony", may sometimes come to serve as a manipulation instrument in and by language, and, even, as a condemnation instrument of the suspect/defendant.